Implementasi Nilai Toleransi Beragama pada Pegawai di lingkungan Badan Perencanaan Penelitian dan Pengembangan Daerah (Bappeda) - Nurma Hutari; Adisel Adisel; Qolbi Khoiri (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
The objectives of the study were (1) to find out the implementation of religious tolerance values ​​among employees within the Bappeda of Bengkulu Province, (2) to describe the faktors supporting the implementation of religious tolerance values ​​to employees within the Bappeda of Bengkulu Province. The type of research used is descriptive qualitative with data collection techniques using interviews, observation and documentation and analyzed using data reduction, data presentation and data verification. The results of the study show that implementation can be seen from 3 indicators, namely: Policy, Implementation and Behavior of Religious Tolerance. The conclusions of the research are (1) the implementation of the value of religious tolerance on employees within the Bappeda of Bengkulu Province has been going well and there has never been a violation of tolerance behavior; (2) The supporting faktor for implementing the value of religious tolerance for employees within the Bappeda of Bengkulu Province is an attitude of respect and appreciation that has been internalized within each individual. Keywords : Bappeda, Implementation, Tolerance Value.